Body fat percentage is a key factor in elevated plasma levels of caffeine and its metabolite in women - Przemysław Domaszewski; Mariusz Konieczny; Paweł Pakosz; Jakub Matuska; Anna Poliwoda; Elżbieta Skorupska; Manel Santafe (PeerJ)
Background Caffeine (CAF) intake is measured in absolute daily amounts or doses per kilogram of body weight. However, both methods are not entirely appropriate. The activity of liver enzymes that metabolise caffeine may be reduced in obese individuals, and plasma caffeine concentrations may vary depending on the fat-to-free-fat mass ratio. This study investigates the relationship between, between body fat percentage and the plasma concentrations of caffeine and its metabolites in women. Methods This experimental study with a between-group comparison design included 38 women (age 25.5 ± 2.7 years; body weight 66.5 ± 15.3 kg). Body fat percentage was measured using bioimpedance analysis (mBCA 515 SECA analyzer), and participants were categorized as non-obese (≤30% body fat, n = 14) or obese (>30% body fat, n = 24). Both groups received a dose of 6 mg/kg body weight of caffeine. Blood samples were taken 60 min after caffeine ingestion, and the concentrations of caffeine and its metabolites in plasma were determined by high-pressure liquid chromatography. The Mann-Whitney U test assessed CAF, paraxanthine (PX), and theobromine (TB) concentrations, while Spearman’s correlation analyzed variable relationships. General linear model (GLM) compared caffeine metabolite levels, and GPower determined the required sample size (44) for large effects. Results The results showed that the obese group had significantly higher caffeine (Mdn = 10.64 vs. Mdn = 2.32) and PX concentrations (Mdn = 1.73 vs. Mdn = 0.85) compared to the non-obese group, with significant differences (p < 0.001 and p = 0.007, respectively). However, no significant difference in TB concentration was observed (p = 0.486). A linear model revealed that group membership significantly influenced CAF concentration (p < 0.001), explaining 56.8% of its variance. PX and TB concentrations showed poor model fits, with minimal explanatory power from group, age, fat mass, and body mass index (BMI). Correlation analysis found strong associations between CAF concentration and fat mass (rho = 0.689). Conclusions Higher body fat percentage is associated with increased plasma caffeine and paraxanthine concentrations following a weight-based caffeine dose. These findings suggest that body fat percentage may be a more relevant factor than total body weight in caffeine metabolism, with potential implications for personalized caffeine dosing guidelines.